The Correlation Between Protein Intake And Muscle Mass in Breast Cancer Patients at Dr. H. Abdul Moeloek Regional Hospital - Mastuti, Yuni; Akhriani, Mayesti; Junita, Dera Elva; Muharramah, Alifiyanti (JURNAL KESMAS DAN GIZI (JKG), 2024)
Breast cancer is the second-leading cause of death among women. Since protein serves as a building ingredient for cells, muscles, and tissues, eating enough of it is thought to be essential for gaining muscle mass. The cornerstone for cancer patients to maintain and/or gain muscle mass will be an adequate protein intake. In this study, breast cancer patients' muscle mass was measured and a 24-hour recall of their weekdays and weekends was conducted. The average amount of protein consumed by participants was 31.22 grams, and the average percentage of muscle mass was 24.02%. The purpose of this study is to ascertain how breast cancer patients' protein consumption and muscle mass relate to one another. This study uses quota sampling as the sample method and a cross-sectional design. There were fifty-six responders in the sample. This research uses the Spearman rank. The normality test results show that the significance value for muscle mass is p value = 0.016 (p < 0.05), it can be concluded that the data is distributed abnormally. Meanwhile, the normality test results for protein intake p-value = 0.200 (p > 0.05) can be concluded that the data is normally distributed, so it is continued with the Spearman rank correlation test. Based on the results of the Spearman rank correlation test, a correlation coefficient value of 0.488 was obtained with a significance p-value of 0.0001. So there is a positive significant correlation between protein intake and muscle mass in breast cancer sufferers at Dr. H. Abdul Moeloek Regional Hospital of Lampung Province p value = 0.0001 (p<0.05).